Floristic diversity in Valley of Flowers National Park, Indian Himalayas - Bisht, Monika; Sekar, K. Chandra; Kant, Rajni; Ambrish, Kumar; Singh, Paramjit; Arya, Dhani (Phytotaxa, 2018)
Floristic diversity of Valley of Flowers National Park, Uttarakhand, a world heritage site in Indian Himalayan Region has been documented. A total of 614 taxa (609 species, 3 subspecies and 2 varieties) belonging to 277 genera and 70 families have been recorded. Among these, 31 plant species are under different threat categories, 05 endemic and one plant namely Cuscuta europaea recorded as invasive. The paper, for the first time, records 72 plant species as additions to flora of Valley of Flowers National Park. Importance of floristic diversity and conservation needs are also discussed.